Análise dialética de linhagens de milho-pipoca para resistência à ferrugem tropical (Physopella zeae) - Sanches, Rafael Egéa (2010)
The second greatest producer of popcorn is Brazil, one of the biggest difficulties is the low productivity, because it is more liable to diseases. The objective was to evaluate the generic resistance of Hybrids of popcorn li neage to Physopella zeae. The experiment was lead at UEM. Making use of 36 simple Hybrids derivatives of the dialélicos crossings between the lineage (L1.1 Zélia, L3.2 Cms 42, L4.4 Cms 43, L7.1 UEM M2, L8.4 Zaeli, L9.1 IAC 112, L9.2 IAC 112, L9.3 IAC 112 e L7.4 UEM M2) of popcorn with four commercial witnesses (Zélia, Jade, IAC 112 e IAC 125) . To inoculum were collected uredospores in infected corn leaves, suspense in water with a drop of Tween 20, inoculated by pulverizati on in susceptible cultivation . The y passed by agitation and the concentration was standarded to 1.5 X 105 uredospores/mL. The inoculation by pulverization leaving for 14 hours de humid chamber in vegetation home. After 14 days, an evaluation of the sick leaf area percentage was done (SLAP ), and the average of the affected leaf area (SLAPA). They were evaluated the same way on the 21th day obtaining the sick leaf area percentage II (SLAP II) and the average of the affected leaf area II (SLAPA II). It was determined the area below the diseas e curve progress and the area below the avera ge disease curve progress. The delineation was in randomized blocks, with 40 treatments in three repetitions. The data were subdued to variance analysis and the test T in level of 10 % of probability and diallel s analysis. Results from the anava revealed differences to SLAP, SLAPA, ABDCP and ABADCP. In relation to SLAP, it is pointed out the Hybrid L4.4 CMS 43 X L9.1 IAC 112, overcoming 21 of the genotypes. To SLAPA the L3.2 CMS 42 X L7.4i UEM M2 presented low val ue with 23,55%. On the feature ABDCP the L4.4 CMS 43 X L9.1 IAC 112 overcame 16 of the genotypes, presenting value of 227,00. To ABADCP stand out the L3.2 CMS 42 X L7.4 UEM M2. The results of the dialectics whole analysis revealed significant differences ( P<0, 10) to the characters SLAP, SLAPA, and ABADCP. To SLAP, SLAPA and ABADCP analyzed in CGC, the lineage L7.4 UEM - M2, was the one that most contributed to the resistance. The major negative estimative to CEC was from L4.4 CMS 43 X L9.1 IAC 112, to SLAP and SLAPA, to ABADCP was the L1.1 Zelia X L3.2 CMS 42.